Multiple developmental craniovertebral junction anomalies associated with fusion of the third and fourth cervical vertebrae: A case report and review of the literature - Himanshu Mishra,; Amit Kumar,; Hitnarayan Prasad,; Sanjay Kumar Suman, (Indian Journal of Case Reports, 2021)
Craniovertebral junction (CVJ) is formed by the occipital condyles of the skull, atlas (C1), and axis (C2). CVJ anomalies are a complex group of disorders with a variable course and complicated line of management. A cross-sectional imaging is indispensable for the evaluation of CVJ as it may unmask pathologies unsuspected by clinical evaluation and conventional radiography. We present a case report in which we describe multiple developmental CVJ anomalies in a 25-year-old male patient. These include fusion defects of anterior and posterior arches of C1, os odontoideum, atlantoaxial subluxation (with compression of the cervical cord at the cervicomedullary junction), and fusion of C3 and C4 vertebral bodies as well as posterior elements.